Ruling out dark matter interpretation of the galactic GeV excess by gamma-ray data of galaxy clusters. Issue 1 (December 2017) - Chan, Man; Leung, Chung
Abstract Recently, some very tight constraints of annihilating dark matter have been obtained from gamma-ray data of the Milky Way and Milky Way dwarf spheroidal satellite galaxies. In this article, we report that there are two excellent galaxy clusters (A2877 and Fornax) which can provide interesting constraints for annihilating dark matter. The lower limits of the dark matter mass for the thermal relic annihilation cross section are 25 GeV, 6 GeV, 130 GeV and 100 GeV respectively for thee + e −, μ + μ −, τ + τ − and $$b\bar{b}$$ b b ¯ channels. For some configuration of our working assumptions, our results improve the Fermi-LAT upper limits of annihilation cross sections by a factor of 1.3 − 1.8 for wide ranges of dark matter mass fore + e −, μ + μ − and $$b\bar{b}$$ b b ¯ channels, and a factor of 1.2–1.8 forτ + τ − channel with dark matter mass ≤100 GeV. These limits basically rule out most of the existing popular dark matter interpretation of the GeV excess in the Milky Way.